Oxford children's classics: The secret garden for grade 7 - Burnett, Frances Hodgson (Pakistan : Oxford university press, 2025)
The Secret Garden tells the story of Mary Lennox, a spoiled and lonely girl sent to live with her uncle in a gloomy Yorkshire mansion after her parents$1 (Bdeath. There, she discovers a locked, neglected garden and, with the help of new friends Dickon and Colin, brings it back to life. As the garden blooms, so do their friendships, health, and happiness. The novel celebrates friendship, healing, and the restorative power of nature.s
Keywords: English Literature - Text Book